MENELAAH KEPEMIMPINAN PEREMPUAN DI PONDOK PESANTREN AL- ISLAM KEMUJA - Wulpiah, Wulpiah (NOURA: Jurnal Kajian Gender dan Anak, 2018)
Discourse about women and leadership is always interesting to study with various perspective. In this context, Islam is a religion that gives the same right for everyone to contribute to the public and domestic domain, regardless of gender, social status, because what distinguishes them at the level of human devotion itself. This study of this issue continuous to find momentum, ut ironically attention almost never given to women who have an important role in Islamic science. Likewise there are women have a crucial role in the formation of Islamic education of institution such as mandrasah and others. It turns out that the pesantren culture requires that the religio-sociological factors become very important for woman to play an active role in the public sphere. If examined the excistence of ewomen in Al Islam Kemuja noarding school, as long as the writer know since its establishment, including when she was educated there, there is no found a woman or ustadzah who holds the top leadership leader at this pesatren. This study shows that until now, woman/ustadzah are only in the domestical realm, its mean attached to the duties of woman; for example dealig with consumtion or guarding of a girls at pesantren. This is not about gender discrimination but the absence of woman has the capacity and capability to occupy these position, also in the culture of community. If there are woman who take part, this is permissible as long as they get permission from their husband.